Distribution and validation of genotypic and phenotypic glyphosate and PPO-inhibitor resistance in Palmer amaranth (Amaranthus palmeri) from southwestern Nebraska. (9th February 2021) - Oliveira, Maxwel C; Giacomini, Darci A; Arsenijevic, Nikola; Vieira, Gustavo; Tranel, Patrick J; Werle, Rodrigo
Abstract: Failure to control Palmer amaranth with glyphosate and protoporphyrinogen IX oxidase (PPO)-inhibitor herbicides was reported across southwestern Nebraska in 2017. The objectives of this study were to 1) confirm and 2) validate glyphosate and PPO-inhibitor (fomesafen and lactofen) resistance in 51 Palmer amaranth accessions from southwestern Nebraska using genotypic and whole-plant phenotypic assay correlations and cluster analysis, and 3) determine which agronomic practices might be influencing glyphosate resistance in Palmer amaranth accessions in that location. Based on genotypic assay, 88% of 51 accessions contained at least one individual with amplification (>2 copies) of the 5-enolypyruvyl-shikimate-3-phosphate synthase ( EPSPS ) gene, which confers glyphosate resistance; and/or a mutation in the PPX2 gene, either ΔG210 or R128G, which endows PPO-inhibitor resistance in Palmer amaranth. Cluster analysis and high correlation (0.83) between genotypic and phenotypic assays demonstrated that EPSPS gene amplification is the main glyphosate resistance mechanism in Palmer amaranth accessions from southwestern Nebraska. In contrast, there was poor association between genotypic and phenotypic responses for PPO-inhibitor resistance, which was attributed to segregation for PPO-inhibitor resistance within these accessions and/or the methodology that was adopted herein. Genotypic assays can expedite the process of confirming known glyphosate and PPO-inhibitor resistance mechanisms in Palmer amaranth from southwestern Nebraska and other locations. Phenotypic assays are also a robust method for confirming glyphosate resistance but not necessarily PPO-inhibitor resistance in Palmer amaranth. Moreover, random forest analysis of glyphosate resistance in Palmer amaranth indicated that EPSPS gene amplification, county, and current and previous crops are the main factors influencing glyphosate resistance within that geographic area. Most glyphosate-susceptible Palmer amaranth accessions were found in a few counties in areas with high crop diversity. Results presented here confirm the spread of glyphosate resistance and PPO-inhibitor resistance in Palmer amaranth accessions from southwestern Nebraska and demonstrate that less diverse cropping systems are an important driver of herbicide resistance evolution in Palmer amaranth.